Transcatheter Aortic Valve Replacement and Concomitant Mitral Regurgitation - Stähli, Barbara E.; Reinthaler, Markus; Leistner, David M.; Landmesser, Ulf; Lauten, Alexander (Frontiers in Cardiovascular Medicine, 2018)
Mitral regurgitation frequently coexists in patients with severe aortic stenosis. Patients with moderate to severe mitral regurgitation at the time of transcatheter aortic valve replacement are at increased risk of future adverse events. Whether concomitant mitral regurgitation is independently associated with worse outcomes after TAVR remains a matter of debate. The optimal therapeutic strategy in these patients - TAVR with evidence-based heart failure therapy, combined TAVR and transcatheter mitral valve intervention, or staged transcatheter therapies - is ill-defined, and guideline-based recommendations in patients at increased risk for open heart surgery are lacking. Hence, a thorough evaluation of the aortic and mitral valve anatomy and function, along with an in-depth assessment of the patients’ baseline risk profile, provides the basis for an individualized treatment approach. The aim of this review is therefore to give an overview of the current literature on mitral regurgitation in TAVR, focusing on different diagnostic and therapeutic strategies and optimal clinical decision making.